Ohne Titel (The Pre-Death Bequest of Gerd Spittler, 2005)
Detailaufnahme einer Flöte (Mundstück?)
Keywords: Photography; Anthropology; Musical instruments; Flute; Photographs; Sammlung Gerd Spittler; Flute (Instrument)